Removal of amitraz from aqueous solutions on clay by adsorption technique at industrial scale - Gulen, Jale; Altin, Zehra; Ozgur, Mahmure (CARL HANSER VERLAG, 2017)
Amitraz (AZ) that is used as acaricide was extracted by using clay adsorbent. The experimental data were modeled via Langmuir and Freundlich isotherms in which adsorption data fit well. The monolayer adsorption capacity was found as 28.53 mg x g(-1) at a temperature of 30 degrees C. The effects of the phases contact time, the initial solution pH value and the initial pesticide concentration were investigated regarding the points of adsorption equilibrium and yield. The adsorption kinetics were investigated by applying pseudo-first-order, pseudo-second-order and intra-particle diffusion laws. Adsorption of AZ was found to be best fitted by the pseudo-second-order model. The intra-particle diffusion also plays an important role in adsorption phenomenon. This adsorption is a physical and spontaneous phenomenon. The pesticide removal by adsorption technique was successfully applied in industrial plants.
Keywords: Adsorption; Amitraz; Clay; Isotherms; Kinetics; Thermodynamic; ACTIVATED CARBON; TICK CONTROL; METAL-IONS; SORPTION; CHROMATOGRAPHY; EQUILIBRIUM; DEGRADATION; ADSORBENTS; HYDROLYSIS; Materials Science